PLODs: Novel prognostic biomarkers and potential immunotherapy targets for head and neck squamous cell carcinoma. Issue 2 (February 2023) - Gong, Siming; Wu, Changwu; Duan, Yingjuan; Fu, Jinfei; Wang, Yuling; Wu, Hao; Zhang, Bixi; Tang, Juyu; Wu, Panfeng
Abstract: Head and neck squamous cell carcinoma (HNSCC) comprise a group of malignant tumors arising from the squamous epithelium of the oral cavity, pharynx, and larynx. HNSCC is the 6th most common cancer in the world, with approximately 650, 000 new cases and 400, 000 deaths annually. Although survival rates have improved, HNSCC therapy may result in short – or long-term morbidity in approximately 50% of cases. Previous studies have also indicated that the overexpression of procollagen-Lysine, 2-Oxoglutarate 5-Dioxygenases (PLOD) family proteins could lead to certain diseases or even tumors. However, there has been no dedicated evaluation of the relationship between PLOD family members and HNSCC. Here we used data from the Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), and Human Protein Atlas (HPA) databases to explore the potential role of PLOD family proteins in HNSCC. Our evaluations suggest that increased expression of PLOD family proteins may be associated with poorer prognosis and increased immune infiltration in HNSCC, making these proteins a potential biomarker for personalized treatment of HNSCC.